Bioengineered Zinc Oxide Nanoparticle-Loaded Hydrogel for Combinative Treatment of Spinal Cord Transection - Lin, Sen; Zhao, Hao-sen; Xu, Chang; Zhou, Zi-peng; Wang, Da-hao; Chen, Shu-rui; Mei, Xi-fan (Frontiers in Bioengineering and Biotechnology, 2022)
Spinal cord injury (SCI) is one of the most destructive diseases. The neuroinflammation microenvironment needs comprehensive mitigation of damages. Thus, regulation of local, microenvironment drugs could be a potential effective treatment. However, clinical studies on SCI with common treatment have reported it to cause systemic toxicity and side effects. Zinc oxide nanoparticles (ZnONPs) have been widely reported to have satisfying anti-inflammation function. Furthermore, green synthesis procedures can improve the capability and possible utilization of ZnONPs. However, the efficient administration and underlying mechanism of ZnONPs in SCI treatment remain unclear. Herein, an innovative approach was built by utilizing ZnONPs loaded in a skeletal muscle-derived adhesive hydrogel (ZnONPs-Gel). Different from the systemic application of ZnONPs, the local administration of ZnONPs-Gel offered the ZnONPs-loaded extracellular matrix with beneficial biocompatibility to the injured spinal cord, thereby promoting effective function recovery. Mechanistically, the ZnONPs-Gel treatment not only markedly reduced ROS production but also decreased apoptosis in the injured spinal cord. Therefore, the strategy based on local administration of the ZnONPs-Gel in the early stage of SCI may be an effective therapeutic treatment.